Eugenol as an efficient anesthetic for neotropical fish Prochilodus nigricans (Teleostei, Prochilodontidae) - R.M. Viegas; C.L. França; J.S. Castro; J.J.P. Castro; T.C. Santana; M.P.G. Costa-Lima; R.N.F. Carvalho Neta; C.R.P. Carreiro; E.G. Teixeira (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2020)
ABSTRACT The use of anesthetics in fish farming is essential to reduce stress during management. The present study proposes to evaluate the effect of eugenol as an anesthetic for the management of curimatã (Prochilodus nigricans). Fifty specimens were used (221.34±9.0 g; 25.8 ±1.1 cm), submitted to five treatments with concentrations of 0, 25, 50, 100 and 200 mgL−1 eugenol for 10 min. The times required to reach each anesthetic stage and the recovery of each fish were recorded. To check bloodglucose levels individual blood samples were taken from the fish before immersion and after ten minutes of anesthetic exposure. Evaluation of the anesthetic effect ongills was performed by histopathological analysis. The concentration of 50 mgL−1 was within the ideal limit of three minutes recommended for surgical anesthesia induction and did not significantly increase glucose levels when compared to the control group (35.7±19.4 mg dL−1), besides not causing gill injuries. At this concentration the fish presented controlled blood glucose levels within the basal levels, besides not taking the risk to have later problems concernig mortality, because this concentration ensures the good health of the gills and good recovery of the animals.